Implementasi Kebijakan Merdeka Belajar dalam Pembelajaran Pendidikan Agama Kristen disekolah Menengah Atas - Harryandi Simanjuntak; Ordekoria Saragih (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Curriculum is very important in education. The Merdeka Curriculum brings a new way of teaching and learning between students and teachers. Christian religious education is also implemented in the Merdeka curriculum. As a subject that must instill Christian values. PAK teachers must prepare a lesson plan sheet and various new strategies in teaching that are based on students' freedom to develop their experiences and skills.